THE EFFECT OF MATHEMATICAL DISPOSITION AND LEARNING MOTIVATION ON PROBLEM SOLVING: AN ANALYSIS - Masta Hutajulu; Tommy Tanu Wijaya; Wahyu Hidayat (Jurnal Infinity, 2019)
This research was motivated by the low problem-solving abilities, mathematical disposition, and learning motivation of junior students. This study aims to find and analyze the influence of mathematical dispositions empirically and learning motivation on problem-solving abilities. Samples were obtained in class VII-2 at SMPN 2 Cimahi as many as 34 students.  The study uses quantitative correlational methods. The analysis was done by a regression method. The data collection was given two pieces of study instruments, namely problem-solving test instruments and non-test questionnaires in a set of mathematical dispositions and learning motivation. The data were tested for regression and correlation. The results of data analysis that was a mathematical disposition and learning motivation were significantly influenced by the problem-solving ability of junior students, with the regression equation Y = 1.95 + 0.121X1 + 0.015X2 indicating a positive influence, and the degree of closeness is the Pearson correlation coefficient of 0.827 classified in a robust positive interpretation. Together, mathematical disposition variables and learning motivation variables can determine the problem-solving variable by 68.3%. Recommendations from this study, teachers should design learning processes that can improve mathematical disposition and student motivation so that students' problem-solving abilities increase.